Strategi Pengembangan Pantai Dalam Rangka Meningkatkan Kelayakan Pariwisata Pantai Seribu Ranting - Santi Andriyani; Nabilla Waviroh; Nur Isnaini Musdyalifah; Faiz Taufikurrohman (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Thousand Branches Beach is a beach that has its own charm, namely in the processing of existing twigs to be made into various works by the Classical Group. This beach is located in Panggung Village, Kedung District, Jepara Regency. Since the Covid-19 pandemic, Thousand Branches Beach has received a fairly large impact such as its declining attractiveness, this can be seen in the various works of tree branches that were damaged because they were not maintained. Many damaged photo spots, scattered garbage and grass that grows wild around the beach make the coastal land increasingly worn and arid. The purpose of this service is to help improve the feasibility of the Thousand Branch Beach as a tourist attraction in Jepara. Community service activities were carried out on March 18-2 2022 which took place in Panggung Village, Kedung District, Jepara Regency. The activities carried out are cleaning the beach, making photo spots and reforestation on the Thousand Branches Beach by involving the active role of the community around the beach, especially the Classical Group. The beach looks cleaner and more well-maintained after all activities are carried out properly, so the strategy in developing this beach makes the Thousand Branches Beach look more feasible than before.